Determining the level of service measures to evaluate service quality of fixed-route shared motorized para-transit services. (January 2021) - Sharma, Deepa; Pandit, Debapratim
Abstract: Fixed route shared motorized para-transit services works as a feeder from neighborhoods to public transit routes and also along transit corridors. These services play an important role in catering to the gaps left by existing public transit systems in developing countries. These services are similar to public transit in various aspects, though there are differences in the operation, organization, and ownership of both the services. Lack of formal regulatory policies and benchmarks plague these services which result in various service quality issues. Thus, there is a need to determine the level of service measures or scales to evaluate the service quality of the system. To accomplish this task, the level of service measures has been developed for different attributes of the system based on user perception. It would help transport authorities in cities to set acceptable and safe service delivery levels in the form of regulations. This research has been conducted in Kolkata, India where user perception data has been collected from para-transit users. The LOS scales have been developed using both existing and novel methods both for quantitative and qualitative service attributes. The results indicate that the existing service level is found to be poor for qualitative attributes in comparison to quantitative attributes and users have lower tolerances for para-transit services compared to bus services. Highlights: LOS scale values for quantitative and qualitative attributes of fixed route shared para-transit services based on user perception. Both existing and novel methods are proposed for determining LOS scale values. Users have lower tolerances for para-transit services compared to bus services. Existing service level is found to be poor for qualitative attributes in comparison to quantitative attributes. Study could also help in framing formal regulatory policies for para-transit.